Flood Modelling Studies Using River Analysis System (HEC-RAS) For Flood Plain Area in Muar City - Mohammad Razi, Mohd Adib; Zahfrin Deli, Muhd Azim; Mohd Yusoff, Mohd Azlan; Anjang Ahmad, Mustaffa; Adnan, Mohd Shalahuddin (International Journal of Integrated Engineering, 2022)
Floods are the most frequent type of natural disaster and occur when heavy precipitation for days or even weeks. Floods will cause extensive destruction, resulting in loss of life and disruption to personal property and vital infrastructure for public health. In this study, HEC-RAS model was used to identify the flood prone area and to determine cross section at floodplain area along the stream network. The study was conducted in the area Muar, Johor. The methodology involved collection of parameters such as length of stream, lateral & elevation of coordinates, streamline and flow data to perform a hydraulic simulation. Different value of flowrate had been used by using the manning equation to estimate the drainage or channel capability to manage the flowrate. The number of station for each cross section need to locate in order to simulate the cross section along the river or channel. Meanwhile, the result outcome will show the cross section for each station. From the result, the analysis of the cross section include with the affected area of floodplain was identified. According to the hydraulic model generated by HEC-RAS software, 7 of 20 stations found will be flood for the 10 years return period since they were unable to accommodate the water flow. By doing this research, the flood model will be developed and HEC-RAS software is one of the tool that can analyse and model for the floodplain area. In a meantime, the government can control and give an early warning about the flood incident.